Ambiente áulico y su influencia en el aprendizaje para niños de primero de educación general básica de la Unidad Educativa Juan E. Verdezoto - Vargas Sánchez, Elsa Marian (2023)
The classroom environment plays a crucial role in the teaching-learning process of school-age children. This research focused on analyzing the educational environment in the "Juan E. Verdezoto" Educational Unit and its influence on the learning of first grade children. Aspects such as the layout of the physical space, the interaction between teachers and students, the integration of information and communication technologies (ICT), and their impact on the emotional well-being and academic performance of students were explored. The results of interviews with three teachers highlighted the importance of creating a safe and emotionally healthy environment, where children can feel confident and supported. The research also highlighted the need to maintain a balance between discipline and creativity in the classroom, which motivates students to actively participate in the educational process. The integration of digital tools and ICT was considered relevant, but the importance of efficient management to avoid distractions was emphasized. In conclusion, it is recommended to promote a safe and emotionally healthy school environment, seek an appropriate balance between discipline and creativity in the classroom, and establish clear guidelines for the integration of technology in the learning process. These recommendations seek to optimize the educational environment and improve the academic performance of first grade students in the "Juan E. Verdezoto" Educational Unit. This study highlights the importance of considering the impact of the classroom environment on children's education and provides a solid foundation for future research and improvements in educational quality.